THE CHEKALIN (LIKHVIN) REFERENCE SECTION IN THE RUSSIAN PLAIN AND ITS SIGNIFICANCE FOR PLEISTOCENE STRATIGRAPHY AND CORRELATION - Bolikhovskaya N.S.; Sudakova N.G. (My University, 1996)
The completeness of the comprehensively studied stratigraphic column comprising the parastratotype of the Belovezh'e Horizon and the stratotypes of the Oka and Likhvin horizons illustrates the great significance of the Likhvin reference section for correlation. A detailed study revealed the age relationships and facial transitions between heterogenous deposits, and allowed us to define the exact positions of the Oka moraine and Likhvin stratotype proper. The periglacial environments were proven to exist prior to the Belovezh'e interglacial stage. This served as the basis for recognizing the Don Horizon in the section. A better understanding of the climatostratigraphic peculiarities of the Belovezh'e palynoflora was achieved. Climatic rhythms were reconstructed for the entire Oka-Dnieper stratigraphic interval. The main objectives were to elucidate the representability and completeness of the Likhvin stratotype, to refine its climatostratigraphic subdivision, and to reveal characteristic features of other interglacial horizons in the section. The climatostratigraphic structure of the Likhvin-Dnieper interval is specified, and new units of the Likhvin Superhorizon are itemized to correct the regional stratigraphic scheme.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен